Methods of development of electromobile charging power stations in Jizzakh city - Rakhmatov, Utkirjon (Science and Education, 2023)
In this article discussed the history of the automotive industry and the current role of electric vehicles in our country and in the world as well. In addition, in order to develop the operation of electric vehicles in Uzbekistan, there is given several ways to improve charging stations in the country.